Strengthening Traditional Villages as Legal Subjects in Tourism Business Management in Bali - Anak Agung Gede Agung Indra Prathama; I Made Suwitra; Ni Luh Made Mahendrawati (Warmadewa Press, 2023)
This study explores the elevation of customary villages' status as legal entities in managing the tourism industry in Bali. Through philosophical, sociological, and empirical legal perspectives, this study investigates the challenges faced in regulating tourism on the island. An empirical legal framework approach is utilized with multi-approaches, relying mainly on the philosophical, historical, and case approaches. The development of the cultural tourism industry in Bali highlights the importance of strengthening local wisdom. The focus of this research includes fundamental questions such as the essence of strengthening customary villages as legal entities in managing the tourism industry, as well as mechanisms that contribute to the strengthening of customary villages in the realm of tourism management. The findings confirm that customary villages play an integral role in directing the tourism industry, by upholding customary laws and pararems and recognizing the unity of customary law communities. This highlights the importance of environmental preservation through Tri Hita Karana principles. Modernization of tourism business management includes digital strategies and the merging of traditional markets with modern markets, with an emphasis on traditional village branding. Strengthening indigenous villages in tourism business management requires cooperation between indigenous villages and the Bali Provincial Government, including profit-sharing schemes. Indigenous villages need capital strengthening through the Village Credit Institution (LPD). The success of tourism management led by indigenous villages depends on the use of customary law as a source of legal certainty in managing tourism based on the principles of Pancasila and Tri Hita Karana. Concrete recommendations include the formulation of tourism management standards involving HR, financial management, tour guides, and service standards. This approach aims to encourage sustainable tourism practices and maintain culture in Bali's Indigenous Villages.